Organizacja terytorialna diecezji chełmskiej i lubelskiej do 1805 roku - Kumor-Mielnik, Joanna (Archiwa, Biblioteki i Muzea Kościelne, 2010)
The following article focuses on the territorial analysis of the diocese of Chełm and Lublin from 1790 to the foundation of the diocese of Lublin by Pope Pius VII in the papal bull on 23 September 1805. The territorial structure of this diocese was formed from the two bigger and two smaller church administrative units, as in 1790 it encompassed some territory which belonged to the Metropolis of Lvov-the diocese of Chełm (three deaneries), as well as most of the Archdeanery of Lublin, which belonged to the diocese of Kraków, the Metropolis of Gniezno(apart from the deanery of Solec). From the latter diocese and metropolis, the deanery of Stężyca (from the deanery of Kielce) and the deanery of Urzędów (from the archdeanery of Zawichost) were also incorporated to the diocese of Chełm and Lublin. Presenting the particular parts of the diocese of Chełm and Lublin created in 1790, the author also describes the years before its foundation, because the analysis of the territorial structures both the diocese of Chełm- erected in 14 the century- and the archdeanery of Lublin-created in 12th century-covers even the beginnings of the 14th century. In addition, in this article an attempt has been made to explain the diocese name controversy –created in 1790- and the titles of its first ordinary bishops: Maciej Garnysz and Wojciech Skarszewski. The boundaries of the diocese of Chełm and Lublin underwent some changes over time due to the partitions of Poland. That is why the following article is accompanied by a few maps, which can help to illustrate each and every modification to the boundaries of the diocese of Chełm and Lublin and to show its parts along with the marked capitals of the deaneries.